Integrating Islamic Values Into Science Instruction to Improve the Scientific Attitude and Character Development of Madrasah Ibtidaiyah Students - Muhammad Suwignyo Prayogo; Siti Aminah; Norshariani Abd Rahman (Unnes Science Education Journal, 2026)
Science learning in Madrasah Ibtidaiyah plays a strategic role in shaping students’ scientific attitudes while fostering character development aligned with Islamic values. However, science learning in many Islamic primary schools still tends to emphasize conceptual mastery rather than integrating moral and religious dimensions. Therefore, this study aims to: (1) analyze the implementation of integrating Islamic values into science learning, (2) examine its contribution to strengthening students’ scientific attitudes, and (3) describe its implications for the character development of Madrasah Ibtidaiyah students. This research employed a qualitative approach using a multi-site study design conducted at MI Miftahul Huda Mlokorejo Jember and MI Ar-Roudhoh Patrang Jember, Indonesia. Data were collected through in-depth interviews, classroom observations, and documentation studies involving ten key informants consisting of madrasah leaders, teachers, and students. The collected data were analyzed using an interactive qualitative analysis model involving data condensation, data display, and conclusion drawing, complemented by cross-site analysis. The results of the analysis reveal that the integration of Islamic values in science learning is implemented systematically through madrasah policies, instructional planning, and teachers’ pedagogical practices. This integration strengthens students’ scientific attitudes, particularly curiosity, scientific honesty, accuracy, and openness to evidence, while also supporting the development of religious character, discipline, responsibility, and social awareness. These findings highlight that integrating Islamic values into science learning provides a holistic pedagogical approach that connects scientific, moral, and spiritual dimensions in Islamic primary education.